Bioaccumulation of metals in the trees of Novi Sad, Serbia. Issue 18 (16th September 2016) - Štrbac, Snežana; Gavrilović, Marjana; Budakov, Ljiljana
ABSTRACT: In urban and industrial areas, higher plants are used as biomonitors of exposure. The objective of this study was to assess metals accumulation in leaves of dendroflora for the city of Novi Sad, Serbia, in May and September. The investigation was conducted at three sites in the urban area of Novi Sad. Determination of metals concentration for Al, As, Cr, Mn, Fe, Co, Ni, Cu, Zn, Cd, and Pb in the sample was performed by inductively coupled plasma–optical emission spectrometry (ICP/OES). In the leaves of the examined tree species the highest concentrations were obtained for: Al, Fe, Mn, and Zn. The highest mean concentrations of metals were present in leaves of Aesculus hippocastanum in September. Trees from Liman and the Danube Park contained higher mean concentrations of metals in the leaves. In A. hippocastanum and Platanus hybrida an increase of al., As, Cr, Fe, and Pb concentrations occurred from May to September, with higher concentrations of Al and Fe noted in May. However, in Celtis australis, Juglans regia, and Tilia platypyllos there was a reduction in Al, Mn, Fe, and Zn from May to September. The basis for these findings requires further investigation, but diverse washing procedures may account partially for these observations.